The Spatial Lay Out of Joglo Pencu House in the Socio Cultural Change the Settlement of Kauman Community in Kudus - Andriansyah, Rico; Triyanto, Triyanto; Iswidayati, Sri (Catharsis, 2018)
Socio cultural life of Kauman community in Kudus Kulon (western Kudus) has changed and influenced the spatial lay out of Kudus traditional house of traditional house, Joglo Pencu. The purpose of this research was to analyze the following problems: (1) how is the socio cultural change in the settlement of Kauman Community in Kudus? and (2) how is the spatial lay out of Kudus traditional house that has been influenced by socio cultural in the settlement of Kauman community in Kudus? Methodologically, this research used qualitative method and observed interdisciplinary. The research data was collected by the technique of observation, interview, and document study. The data validity was used source triangulation. Data analysis was done by reduction, presentation, and verification of data. The research results were; first, the society in Kauman community Kudus Kulon developed influencing the population composition, economic life change, and belief system change. Second, the socio cultural change influences the spatial lay out of Joglo Pencu house. It is suggested to the heir of Kudus traditional house owner to manage the spatial lay out and to maintain it wisely the heritage house. This research is beneficial to the heir of the house and the development of science.